2017
DOI: 10.1097/sla.0000000000002114
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Early Mobilization Within an Enhanced Recovery Program for Colorectal Surgery

Abstract: ClinicalTrials.gov Identifier: NCT02131844.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 46 publications
4
111
1
Order By: Relevance
“…The rising demand for continuous quality improvement in patient care and the need to reduce healthcare costs has led to hospitals introducing accelerated care pathways to decrease patients' length of stay after major surgery (Fiore et al, 2017). With shorter hospital stays there is reduced time and resources available to prepare patients transitioning to home to manage their recovery (Maloney & Weiss, 2008;Weiss, Yakusheva, & Bobay, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The rising demand for continuous quality improvement in patient care and the need to reduce healthcare costs has led to hospitals introducing accelerated care pathways to decrease patients' length of stay after major surgery (Fiore et al, 2017). With shorter hospital stays there is reduced time and resources available to prepare patients transitioning to home to manage their recovery (Maloney & Weiss, 2008;Weiss, Yakusheva, & Bobay, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Wiklund et al observed that goals for steps did not signi cantly improve bowel function recovery or shorten LOS in patients undergoing gastric-bypass surgery (18). Staff-assisted facilitation of early mobilization also did not improve outcomes compared with traditional ERAS care for colorectal surgery (19).…”
Section: Discussionmentioning
confidence: 98%
“…Wiklund et al observed that goals for steps did not significantly improve bowel function recovery or shorten LOS in patients undergoing gastric-bypass surgery (16). Staff-assisted facilitation of early mobilization also did not improve outcomes compared with traditional ERAS care for colorectal surgery (17).…”
Section: Discussionmentioning
confidence: 99%